Long-term prognostic value of the combination of malnutrition and fib-4 index in patients admitted with acute decompensated heart failure. (14th October 2021) - Yamada, T; Watanabe, T; Morita, T; Kawasaki, M; Kikuchi, A; Kawai, T; Seo, M; Nakamura, J; Kayama, K; Fukunami, M
Abstract: Background: Malnutrition is associated with increased mortality risk in patients with acute decompensated heart failure (ADHF). Cardiohepatic interactions have been a focus of attention among heart failure. It was reported that liver stiffness assessed by non-invasive fibrosis marker such as Fibrosis-4 (FIB4) index provide prognostic information in ADHF patients. However, there is no information available on the long-term prognostic value of the combination of malnutrition and FIB4 index in patients admitted for ADHF. Methods and results: We studied 294 patients admitted for ADHF, who were discharged with survival. Nutritional status was evaluated by Geriatric Nutritional Risk Index (GNRI) calculated as follows: 14.89 × serum albumin (g/dl) + 41.7 × BMI/22, and malnutrition was defined as GNRI <92. FIB4 index was calculated by the formula: age (yrs) × AST[U/L] / (platelets [10 3 /μL] × (ALT[U/L]) 1/2 ), and abnormal FIB4 index was defined as >2.67. During a mean follow-up period of 4.3±3.3 yrs, 94 patients had all-cause death. At multivariate Cox regression analysis, GNRI and FIB4 index were significantly associated with the total mortality, independently of prior heart failure hospitalization, systolic blood pressure, and serum creatinine level. Patients with malnutrition and abnormal FIB4 index had a significantly higher risk of the total mortality than those with either and none of them (49% vs 32% vs 20%, p<0.0001, respectively). Conclusions: The combination of malnutrition and FIB4 index might be useful for stratifying ADHF patients at higher risk for the total mortality. FUNDunding Acknowledgement: Type of funding sources: None.